Extracurricular aquatic activities program to promote the physical fitness of university students (RIAF. International Journal of Physical Activity, 2026)
Introduction. The practice of swimming as a function of quality of life and healthy living styles constitutes one of the most proliferating activities today. Objective: to promote the physical condition of university students who attend the swimming program during their free time. Methodology. The study is of a causal explanatory type with an experimental design in the form of a pedagogical pre-experiment (single group) with a cross-sectional quantitative approach, in which a total of (n=21) young university students from different programs at the Milagro State University participated. Results. The results of the program were evidenced by the Student T-test, which yielded a P value of 0.05.
Keywords: Swimming; Fitness; College Students.